What Drives the Zakat Payment Decision at the BAZNAS of South Sumatra? - Eka Octavian Pranata; Irfan Syauqi Beik; Mimin Aminah (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2022)
Promotional strategies have a significant impact on decisions to pay zakat at a zakat institution in the era of digital advancement. This study intends to investigate the determinants of zakat payment at the National Zakat Agency (Badan Amil Zakat Nasional - BAZNAS) of South Sumatra Province, Indonesia, using influencer endorsement and electronic word of mouth as independent variables. A total of 250 people, which were selected using the purposive sampling method, participated in this study. The data was processed and analyzed using Structural Equation Modeling (SEM). The findings indicate that electronic word of mouth strengthens the beneficial relationship between influencer endorsement and the decision to pay zakat at the BAZNAS. The impact of influencer endorsement on zakat payment decisions was shown to be substantially stronger when electronic word of mouth was included as a moderator variable. The finding suggests that the BAZNAS of South Sumatra must play an optimal role in utilizing public figures to promote the BAZNAS' features, as well as increasing information about BAZNAS on social media, so that muzzaki are interested in paying zakat through BAZNAS.========================================================================================================ABSTRAK – Apa yang Mendorong Keputusan Membayar Zakat pada BAZNAS Sumatera Selatan? Strategi promosi berpengaruh signifikan terhadap keputusan membayar zakat pada lembaga zakat di era kemajuan digital. Penelitian ini bertujuan untuk mengkaji determinan pembayaran zakat di Badan Amil Zakat Nasional (BAZNAS) Provinsi Sumatera Selatan, Indonesia, menggunakan influencer endorsement dan electronic word of mouth sebagai variabel independen. Sebanyak 250 orang, yang dipilih dengan menggunakan metode purposive sampling, berpartisipasi dalam studi ini. Data diolah dan dianalisis menggunakan Structural Equation Modeling (SEM). Hasil kajian menunjukkan bahwa electronic word of mouth memperkuat hubungan antara endorsement influencer dengan keputusan membayar zakat di BAZNAS Sumatera Selatan. Dampak influencer endorsement terhadap keputusan membayar zakat terbukti jauh lebih kuat ketika electronic word of mouth dijadikan sebagai variabel moderator. Hasil ini berimplikasi terhadap kebijakan BAZNAS Sumsel dalam mengoptimalkan tokoh-tokoh publik dalam mempromosikan fitur-fitur BAZNAS dan mendiseminasikan lebih banyak informasi mengenai BAZNAS di media sosial, agar muzzaki tertarik membayar zakat melalui BAZNAS.